Cooperative control of electrical bicycles. (June 2021) - Efken, Marc; Kohn, Nils; Greven, Dietmar; Misgeld, Berno J.E.
Abstract: Electric bicycles provide an electric supportive power in addition to the physiological pedalling power of the driver. Electric bicycles thus allow for activities like group rides with people having different degrees of physical fitness. In a group ride, however, each driver would need to adapt the level of electromotive support power (i.e. the assistance level) to the desired level of physiological power output. To overcome this disadvantage, a novel control strategy to automatically adjust the assistance level of the electric bicycle is presented. By this, a uniform velocity can be achieved for all electrical bicycles, while every cyclist applies the amount of power they are most comfortable with. A distributed control approach over a network of electric bicycles is proposed. A reference velocity is calculated by a consensus algorithm. The reference velocity is then used in a local inner feedback loop to adjust the output torque of the support motor. For the velocity feedback loop an H ∞ -controller is designed. The control algorithms are tested with respect to stability and performance in simulation and experiments. Moreover, local and global stability are established by formal methods.